Clinical suspicion of congenital heart diseases during well-baby follow-up and echocardiographic correlation - Adhikari, K. M.; Dhingra, Sandeep (International Journal of Contemporary Pediatrics, 2017)
Background: Congenital heart disease (CHD), the most common cardiac malformation in the fetal and neonatal period, represents a heterogeneous group of defects with little known cause. Despite advances in detection and treatment, CHD accounts for 3% of all infant deaths and 46% of death from congenital malformations. CHD patients with minimum or no symptoms are frequently under diagnosed in areas with inadequate health services. The aim of this study was to investigate the role of clinical suspicion of congenital heart disease in babies who presented for well-baby follow-up against echocardiographic findings and to study the clinical spectrum of all the CHD that were diagnosed. Methods: The study involved analysis of data collected by the authors while working in a tertiary care center at Mumbai, India, during 2009 to 2010. All the babies born from April 2009 to August 2010 (17 months) and those who came for well-baby visits (with or without symptoms) were examined carefully for findings on cardiac examination including abnormalities of heart sound and presence of murmur on auscultation. Findings of the echocardiography were recorded for follow up and all the babies were followed up on at least three-monthly basis. Echocardiography was repeated on a quarterly basis in symptomatic babies and six-monthly basis in asymptomatic babies with small septal defects. All the babies on follow up were closely monitored clinically and on echocardiography for ascertaining the natural course of the observed defects. Results: A total of 1856 babies were born at the tertiary care center out of which 1688 were seen at the well-baby clinic. A total of 42 cases were referred for echocardiography on clinical suspicion of CHD and out of these 21 (50%) were positive for some form of CHD. Most common CHD diagnosed was atrial septal defect (ASD). There was no spontaneous closure of ventricular septal defects (VSD), though, 02 cases of ASD less than 3 mm closed during the during the follow up period. Conclusions: This study demonstrated that clinical experience is a valuable tool in early diagnosis of CHD, even if they are asymptomatic. Early echocardiography is justified to diagnose the cases so that appropriate follow-up and management decisions could be planned. Though majority of the cases were moderate to small ASD and VSD, there is a need to diagnose them early and follow them up till closure.